FAMILY EXPERIENCE IN PERFORMING HOME EMERGENCY FIRST AID FOR CHILDREN HAVING A FEBRILE SEIZURE: FAMILY EXPERIENCE IN PERFORMING HOME EMERGENCY FIRST AID FOR CHILDREN HAVING A FEBRILE SEIZURE - Tri Widyastuti, Tri Widyastuti Handayani; Dyah Dwi Astuti (POLTEKKES KEMENKES YOGYAKARTA, 2024)
Home emergency aid for children having a febrile seizure determines the results of health outcomes of the children. The research aimed to obtain the significance and importance of family’s experience in home emergency first aid for children having a febrile seizure. The method used in this research is the qualitative descriptive phenomenology method which consists of four stages, namely bracketing, intuiting, analyzing, and describing. Participants in this research were families who have children under five with a history of febrile seizures. The participants consisted of 10 people and the applied sampling technique was the purposive sampling technique. The analysis of the research results applied the Colaizzi method. The results of this research obtained one theme with four sub-themes, namely letting a febrile seizure run its course, observing, putting something in children's mouths, and asking for help from others. The results of this research recommend the importance of health education in families about home first aid to give when children have a febrile seizure.